2000
DOI: 10.1034/j.1600-0676.2000.020004296.x
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor in human liver cirrhosis

Abstract: Overexpression of CTGF in liver cirrhosis, especially in fibroblasts/myofibroblasts and stellate cells, suggests that this novel factor may play an important role in hepatic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 0 publications
2
74
0
3
Order By: Relevance
“…CTGF acts as a downstream effector of TGF-b1 to stimulate fibrotic processes, promoting fibroblast proliferation, migration, and ECM production [23]. Overexpression of CTGF in liver cirrhosis, especially in fibroblasts/myofibroblasts and stellate cells, shows its important role in hepatic fibrosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…CTGF acts as a downstream effector of TGF-b1 to stimulate fibrotic processes, promoting fibroblast proliferation, migration, and ECM production [23]. Overexpression of CTGF in liver cirrhosis, especially in fibroblasts/myofibroblasts and stellate cells, shows its important role in hepatic fibrosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that upregulation of CTGF might be a central pathway during HSC activation and hepatic fibrogenesis by mediating many of the profibrotic effects of TGF-␤ (1,41,42,53). CTGF expression in HSCs is significantly enhanced during the process of activation in vitro and in vivo (41,53).…”
mentioning
confidence: 99%
“…[21][22][23] In addition, we and others have shown in previous works that CTGF was involved in liver fibrosis both in human chronic liver diseases and in experimental models of liver fibrosis in rats. [24][25][26] In our own study, CTGF expression was significantly associated with scores of fibrosis in chronic hepatitis, and CTGF immu-nostaining identified hepatic stellate cells (HSC) as the main source of CTGF. 24 Because NASH, a disease commonly associated with hyperglycemia and insulin resistance, is now recognized as a chronic liver disease that may lead to cirrhosis, we were interested in studying the expression of CTGF in the context of this disease both in humans and in an animal model of obesity and diabetes.…”
mentioning
confidence: 99%